Transitioning health workers from PEPFAR contracts to the Uganda government payroll - Zakumumpa, Henry; Rujumba, Joseph; Amde, Woldekidan; Shumbusho Damian, Respicius; Maniple, Everd; Ssengooba, Freddie (Health Policy and Planning, 2021)
Although increasing public spending on health worker (HW) recruitments could reduce workforce shortages in sub-Saharan Africa, effective strategies for achieving this are still unclear. We aimed to understand the process of transitioning HWs from President’s Emergency Plan for AIDS Relief (PEPFAR) to Government of Uganda (GoU) payrolls and to explore the facilitators and barriers encountered in increasing domestic financial responsibility for absorbing this expanded workforce. We conducted a multiple case study of 10 (out of 87) districts in Uganda which received PEPFAR support between 2013 and 2015 to expand their health workforce. We purposively selected eight districts with the highest absorption rates (‘high absorbers’) and two with the lowest absorption rates (‘low absorbers’). A total of 66 interviews were conducted with high-level officials in three Ministries of Finance, Health and Public Service (n=14), representatives of PEPFAR-implementing organizations (n=16), district health teams (n=15) and facility managers (n=22). Twelve focus groups were conducted with 87 HWs absorbed on GoU payrolls. We utilized the Consolidated Framework for Implementation Research to guide thematic analysis. At the sub-national level, facilitators of transition in ‘high absorber’ districts were identified as the presence of transition ‘champions’, prioritizing HWs in district wage bill commitments, host facilities providing ‘bridge financing’ to transition workforce during salary delays and receiving donor technical support in district wage bill analysis—attributes that were absent in ‘low absorber’ districts. At the national level, multi-sectoral engagements (incorporating the influential Ministry of Finance), developing a joint transition road map, aligning with GoU salary scales and recruitment processes emerged as facilitators of the transition process. Our case studies offer implementation research lessons on effective donor transition and insights into pragmatic strategies for increasing public spending on expanding the health workforce in a low-income setting.
Keywords: Human Resources for Health; Health systems; Decentralization; HIV; Donor transition; Implementation research; Overseas development assistance